Bone Metabolism Impairment in Heart Transplant: Results From a Prospective Cohort Study. Issue 4 (April 2020) - Seguro, Luis F.B.C.; Pereira, Rosa M.R.; Seguro, Luciana P.C.; Caparbo, Valeria F.; Avila, Monica S.; Mangini, Sandrigo; Campos, Iascara W.; Gaiotto, Fabio A.; Marcondes-Braga, Fabiana G.; Bacal, Fernando
Abstract : Background: Data on the prevention of fractures after heart transplant (HTx) are controversial in the literature. Understanding the effects of HTx on bone may guide appropriate treatments in this high-risk population. Methods: Seventy adult HTx patients were followed for 12 months. Clinical and laboratory parameters, bone mineral density, microarchitecture, and vertebral fractures were assessed at baseline (after intensive care unit discharge) and at 6 and 12 months. Patients received recommendations regarding calcium intake and vitamin D supplementation after HTx. Results: At baseline, 27% of patients had osteoporosis, associated with the length of hospitalization before HTx ( P = 0.001). Bone mineral density decreased in the first 6 months, with partial recovery later. Bone microarchitecture deteriorated, mainly in the trabecular bone in the first 6 months and cortical bone in the subsequent 6 months. At baseline, 92.9% of patients had vitamin D levels <30 ng/mL and 20.0% <10 ng/mL. Patients also had calcium at the lower limit of normal, high alkaline phosphatase, and high bone resorption biomarker. These abnormalities were suggestive of impaired bone mineralization and normalized at 6 months with correction of vitamin D deficiency. The majority of vertebral fractures were identified at baseline (23% of patients). After multivariate analyses, only a lower fat mass persisted as a risk factor for vertebral fractures (odds ratio, 1.23; 95% confidence interval, 1.04-1.47; P = 0.012). Conclusions: High frequencies of densitometric osteoporosis, vitamin D deficiency, bone markers abnormalities, and vertebral fractures were observed shortly after HTx. Calcium and vitamin D supplementation should be the first step in correcting bone mineralization impairment before specific osteoporosis treatment.